Study on the humidification mechanism of asphalt mixtures by modified zeolite - Zhi, Suo; Tao, Hu; Zihao, Zhao; Jiaheng, Hu; Xinxin, Wang; Shijie, Xu (Frontiers in Materials, 2024)
Natural zeolite is commonly used as an adsorbent for road dust suppression due to its excellent moisture absorption properties. However, during the formation process, natural zeolite tends to accumulate some zeolite water, organic impurities, and metal cations that occupy the pore channels and cavities, thereby blocking the passage of water molecules and hindering their adsorption. This study aims to improve the weak moisture absorption rate and capacity of dust suppression asphalt mixtures caused by clogged pores and impurities in natural zeolite. To achieve this different concentrations of salt solutions (NH4Cl, NaCl, MgCl2, and CaCl2) are used as modifiers for the treatment of natural zeolite. Scanning electron microscopy and Fourier transform infrared spectroscopy are used to study the interface and functional group changes between the modified zeolite substrate and asphalt mixture. The nitrogen adsorption/desorption curves of asphalt mixtures with different dosages were obtained using a nitrogen adsorption instrument. Based on this, parameters such as the specific surface area and adsorption pore volume of natural zeolite and modified zeolite asphalt mixtures were calculated using the BET and BJH methods. A macroscopic dust suppression test was further conducted to evaluate the dust suppression effect of the modified zeolite asphalt mixture on PM10.The results show that the moisture absorption rate and capacity of the modified zeolite are significantly improved. 20wt.%CaCl2 modification performs the best, and the moisture absorption capacity of the modified zeolite can reach up 10 times that of natural zeolite.Compared to the natural zeolite asphalt mixture, the specific surface area of the modified zeolite asphalt mixture is increased by 16.52%, and the adsorption pore volume is increased by 44.9%. The addition of modified zeolite powder significantly improves the dust suppression performance of the asphalt mixture. When the dosage of modified zeolite powder reaches 80%, the dust suppression effect reaches its peak, with an improvement of 16.34%.